(untitled) (BioLaw Journal - Rivista di BioDiritto, 2026)
Following the pioneering approach of the UK Climate Change Act, the framework laws on climate change adopted by EU Member States include the best available science into the climate policy-making process through the establishment of specific technical bodies. This paper analyses, from a comparative view, whether and how these technical bodies satisfy the requirements of independence and exercise advisory and monitoring functions on programmes to reduce GHG emissions as well as on their adequacy for reaching national climate objectives. The outcome of the research will be used to identify which emerging solutions in European Comparative Law are most consistent with a credible climate governance.